Innovación y creatividad de los emprendimientos y su incidencia en el desarrollo de los negocios familiares de los sectores urbanos del cantón el empalme, año 2023. - Briones Cusme , Maryuri Carolina (2024)
Urban entrepreneurship is an economic defense mechanism that seeks to address the scarce labor supply in the city, and that depends on the ingenuity of entrepreneurs to be sustainable over time and to create a positive impact on the market and the local economy. . The objective of this research was to analyze the innovation and creativity of family enterprises and as an index in the development of family businesses in the urban sector of the El Empalme canton. The methodology applied was descriptive, with an inductive and deductive approach to the study variables, with an additional analytical and statistical framework, which allowed collecting sufficient data to support the research. Through techniques such as interviews and surveys of those involved, substantial information was obtained to meet the objectives. The results show that innovation and creativity affects business but 48% of respondents have little interest in this topic, as well as that business development is affected by low sales, security and lack of knowledge, accompanied by conformity in attention. In the and, 50% are aware that innovation and creativity increase sales but this can generate accelerated investment and over-indebtedness in entrepreneurs. Innovation and creativity are crucial factors in the growth and sustainability of family businesses since they represent a significant part of local economies that must continually adapt to market changes and consumer needs to remain competitive.